2012
DOI: 10.1126/science.1222978
|View full text |Cite|
|
Sign up to set email alerts
|

UV Dosage Levels in Summer: Increased Risk of Ozone Loss from Convectively Injected Water Vapor

Abstract: The observed presence of water vapor convectively injected deep into the stratosphere over the United States can fundamentally change the catalytic chlorine/bromine free-radical chemistry of the lower stratosphere by shifting total available inorganic chlorine into the catalytically active free-radical form, ClO. This chemical shift markedly affects total ozone loss rates and makes the catalytic system extraordinarily sensitive to convective injection into the mid-latitude lower stratosphere in summer. Were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
243
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(262 citation statements)
references
References 46 publications
7
243
4
Order By: Relevance
“…Numeric simulations have also indicated that the OH in the stratosphere acquires an oxygen isotope anomaly (Δ 17 O = 2-40‰) by means of exchange with NO x (39,42). The anomalous signal of OH and HO 2 in the stratosphere is preserved (39,42) (43,44), which is normally erased in the troposphere due to rapid isotope exchange with water vapor (∼3% in the tropics to 0.1% in the cold polar regions) (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numeric simulations have also indicated that the OH in the stratosphere acquires an oxygen isotope anomaly (Δ 17 O = 2-40‰) by means of exchange with NO x (39,42). The anomalous signal of OH and HO 2 in the stratosphere is preserved (39,42) (43,44), which is normally erased in the troposphere due to rapid isotope exchange with water vapor (∼3% in the tropics to 0.1% in the cold polar regions) (20).…”
Section: Discussionmentioning
confidence: 99%
“…The ITCZ thus links the troposphere to the stratosphere and is an important corridor for the transport of aerosol and trace gases to the stratosphere (49). The maximum transport of water vapor also occurs in the ITCZ (44) in the vicinity of the ENSO region, which also corresponds to the region of the OEI measurements used in Fig. 1B.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes in the chemical composition in this part of the Earth's atmosphere play a crucial role for climate change (e.g., Solomon et al, 2010;Riese et al, 2012;Hossaini et al, 2015). Moreover, increasing stratospheric water vapor has the potential to affect stratospheric chemistry (e.g., Kirk-Davidoff et al, 1999;Dvortsov and Solomon, 2001;Vogel et al, 2011a;Anderson et al, 2012) and can influence the formation of cirrus clouds in the lower stratosphere (Spang et al, 2015). Further, it is discussed that enhanced water vapor in combination with pollution in the Asian monsoon region may play an important role in the formation of the Asian tropopause aerosol layer (ATAL), which causes regional radiative forcing (Vernier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this large-scale transport process of water vapor by air mass exchange between the tropics and the extratropics, convection-induced injections of water vapor in midlatitudes can also occur in large storm systems such as tropical cyclones and by deep continental convection (e.g., Anderson et al, 2012;Homeyer et al, 2014;Vogel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical, radiative and dynamical properties of this region are coupled. Therefore, changes in chemistry in the UTLS may have consequences for tropospheric chemistry (Anderson et al, 2012) and climate (Riese et al, 2012). Additionally, it is possible that future climate change may impact on VSLB transport into the UTLS through changes in oceanic emissions as ocean temperature and acidity change and also through atmospheric processes such as increased convection and large-scale vertical transport (Dessens et al, 2009) or sea surface temperature, wind speed and marine boundary layer height (Hepach et al, 2014).…”
mentioning
confidence: 99%